Co-extrusion of Zircaloy-2 and Zr-Sn alloy for double clad tube manufacturing: Numerical simulation and experimental validation. (March 2019) - Jha, S.K.; Dixit, Saurabh; Chetan, K.; Vaibhaw, K.; Srivastava, D.
Graphical abstract: Abstract: Zircaloy-2 cladding in boiling water nuclear reactors is prone to brittle failure due to pellet-cladding interaction (PCI). The simultaneous effects of stress corrosion cracking and cladding stresses are the main failure mechanisms which limit the life of fuel clad tubes. Zircaloy-2 clad tube, with the inner surface lined with dilute Zr-0.3 wt %Sn layer is a potential and effective protection against PCI failure. Due to the difference in flow behavior of two dissimilar alloys (softer in the core and harder in the sleeve), the manufacturing of double-clad tubes requires proper selection of process parameters. In the present study, manufacturing process has been developed at actual scale to produce metallurgically bonded Zr-Sn lined Zr-2 double clad. Further, this paper systematically brings out the billet assembly methodology using copper jacketing and vacuum degassing. The constraints present in defect-free metallurgical bonding have been overcome by a series of industrial co-extrusion trials of Zr-Sn and Zr-2 composite billet assembly suggested by FEM-based simulation. The co-extrusion process parameters such as strain rate (ram speed), temperature and co-extrusion ratio were suitably optimized using FEM-based analysis of co-extrusion. The metallurgical bond integrity, microstructure evolution and liner thickness variation were characterized by FEG-SEM. The interface between Zr-2 and Zr-Sn was found to be continuous.